Hubungan Pola Asuh Ibu dengan Status Gizi Balita di Wilayah Kerja Puskesmas Oka Kabupaten Flores Timur - Theresia Fransiska Perada Dechantal Niron; Sarci Magdalena Toy; Marselinus Laga Nur (Yayasan Literasi Sains Indonesia, 2025)
Children under five years of age who receive higher quality care tend to have lower morbidity rates and better nutritional status. The problem of malnutrition in Oka Health Center, East Flores in 2023 was 217 children, with details of children with severe underweight of 30 children, underweight of 169 children, and children at risk of being overweight of 18 children. Nutritional problems are closely related to parental care patterns, especially mothers, which are important factors for the nutritional status and health of children under five years of age. Maternal care patterns consist of feeding patterns, health care patterns, and personal hygiene patterns. This study aims to analyze the relationship between maternal care patterns and the nutritional status of under-five children. This study was conducted in the Oka Community Health Center Work Area in August 2024 with a sample of 86 under-five children. Data analysis technique using the Chi-square statistic test. The results of the study showed that feeding patterns (type of food, amount of food and frequency of feeding) (p-value = 0.005 <0.05), health care patterns (utilization of health services, immunization and history of infectious diseases) (p-value = 0.015 <0.05), and personal hygiene patterns (personal hygiene and environmental hygiene) (p-value = 0.010 <0.05) have a significant relationship with the nutritional status of children. It is recommended that parents can improve their knowledge and motivation to pay more attention to child care patterns, especially for children under five years of age.